Post termination interaction in international joint ventures (IJV). Issue 2 (8th April 2019) - Parameswar, Nakul; Dhir, Sanjay
Abstract : Purpose: This paper aims to explore dynamics of post termination interaction between international joint venture (IJV) partners and empirically examines IJV level and dyad level factors that influence the choice of post IJV termination interaction as supplier, complement or competitor. Design/methodology/approach: In-depth literature review is undertaken to identify IJV and dyad level that could influence the choice of post termination interaction between terminated IJV partners. Hypotheses are empirically validated using multinomial logistic regression on data collected on terminated IJV headquartered in India. Findings: The results denote that the choice of post-IJV termination interaction between IJV partners as supplier, complement or competitor is influenced by interdependence, bargaining power, foreign partner's purpose of IJV, complementarity and type of IJV termination. Research limitations/implications: This paper explores an under researched area in extant IJV literature that could be taken up for study by academicians. The paper upholds and strengthens the dynamic capabilities view of strategic management in IJV context. Practical implications: This paper examines a practice adopted by businesses in emerging markets and determines important factors that influence the choice of interaction post IJV termination between partners. Practitioners will be encouraged to understand and plan post termination dynamics with their terminated IJV partner. Originality/value: The paper undertakes examination of a practical business phenomena, i.e. interaction post termination between terminated IJV partners.